Evidence of Digital Marketing Effect on Brand Building: A Case Study of the Apple iPhone - Zakiyah Rahma; Rahul Chauchan; Didi Susianto; Jatiningrum, Citrawati; Hardini Ariningrum (RUBINSTEIN, 2026)
The quality of financial statements remains a critical issue for micro, small, and medium enterprises (MSMEs), particularly because many business actors still face limitations in accounting knowledge, technology use, and practical application of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This study examines the effects of SAK EMKM socialization, accounting comprehension, and information technology on the financial statement quality of micro-scale MSMEs, with SAK EMKM implementation as an intervening variable. A quantitative explanatory survey was conducted on 40 micro-scale MSMEs in Kemiling District, Bandar Lampung, using purposive sampling, and the data were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results show that accounting comprehension significantly affects SAK EMKM implementation (p < 0.001), whereas SAK EMKM socialization (p = 0.112) and information technology (p = 0.216) have positive but statistically insignificant effects. SAK EMKM implementation does not significantly affect financial statement quality (p = 0.581) and does not mediate the relationships between the independent variables and financial statement quality. However, SAK EMKM socialization (p = 0.029) and accounting comprehension (p = 0.040) directly improve financial statement quality. These findings imply that practical accounting training and continuous mentoring are more critical than formal standard exposure or technology provision alone.